Available equipment for traumatic haemorrhage management in Austrian prehospital physician response units: a nationwide survey and analysis of guideline adherence - Michael Eichinger; Michael Eichlseder; Gerald Schützelhofer; Alexander Pichler; Nikolaus Schreiber; Philipp Zoidl; Gabriel Honnef; Paul Zajic (BMC Emergency Medicine, 2024)
Abstract Background Traumatic injuries, particularly those involving massive bleeding, remain a leading cause of preventable deaths in prehospital settings. The availability of appropriate emergency equipment is crucial for effectively managing these injuries, but the variability in equipment across different response units can impact the quality of trauma care. This prospective survey study evaluated the availability of prehospital equipment for managing bleeding trauma patients in Austria. Methods A nationwide survey was conducted across 139 Austrian Prehospital Physician Response Units (PRUs) to evaluate the presence and adherence to guidelines of bleeding control equipment. The digitally distributed survey included questions on equipment types, such as pelvic binders, tourniquets, haemostatic gauze, and advanced intervention sets. Data were analysed against the most recent recommendations and guidelines to assess conformity and identify gaps. Results The survey achieved a 96% response rate, revealing that essential equipment like pelvic binders and tranexamic acid was available in all units, with tourniquets present in 99% of them. However, few services carried advanced equipment for procedures like REBOA or thoracotomy. While satisfaction with the current equipment was high, with 80% of respondents affirming adequacy, the disparities in the availability of specific advanced tools highlight potential areas for improvement, offering a promising opportunity to enhance trauma care capabilities. Conclusions While essential emergency equipment for haemorrhage control is uniformly available across Austrian PRUs, the variation in advanced tools underscores the need for standardised equipment protocols. The urgency for regular kit updates following prehospital guidelines and training is essential to enhance trauma care capabilities and ensure that all emergency response units are equipped to manage severe injuries effectively. This standardisation could lead to improved patient outcomes nationwide.